Meta-analysis of the effectiveness of educational programs about HIV prevention on knowledge, attitude, and behavior among adolescents - Ratnawati, Diah; Huda, Mega H.; Mukminin, Muhammad A.; Widyatuti, Widyatuti; Setiawan, Agus (Narra Sains Indonesia, 2024)
The prevalence of human immunodeficiency virus (HIV) among adolescents is on the rise due to a lack of comprehensive knowledge, leading to suboptimal attitudes and behaviors, which emphasizes the critical need for targeted interventions. The aim of this review study was to evaluate the effectiveness of educational interventions for HIV prevention among adolescents by assessing their impact on knowledge, attitude, and behavior. A systematic review of seven databases: PubMed, Science Direct, Cochrane, JSTOR, Embase, Scopus, and EBSCO were identified, and 14 eligible randomized controlled trials published until June 2023 were included. Two independent authors assessed quality appraisal using the Risk of Bias 2.0. Outcomes were measured using the standard mean difference (SMD) with random effects model and a 95% confidence interval. Subgroup analyses and meta-regression were performed to explore heterogeneity. The results showed significant improvements in participants' knowledge (SMD: 1.13, 95%CI: 0.78–1.49), behavior intentions (SMD: 1.22, 95%CI: 0.37–2.07), and attitude (SMD: 0.48, 95%CI: 0.02–0.95) after receiving HIV prevention education programs. Interventions grounded in theoretical principles and incorporating technology, group settings, and audio-visual aids were found to be effective in enhancing knowledge of HIV prevention and promoting behavioral intentions. Peer-led education positively impacted both knowledge and attitude. Moreover, excluding parents from these programs was identified as a crucial factor in improving adolescents' knowledge of HIV prevention. In conclusion, educational programs focused on HIV effectively enhance adolescents' knowledge, attitudes, and behavioral intentions among adolescents. Professionals planning interventions should consider these impactful components in designing comprehensive strategies.